2015
DOI: 10.2139/ssrn.2612397
|View full text |Cite
|
Sign up to set email alerts
|

A Life-Span Perspective on Life Satisfaction

Abstract: Abstract:The German population is ageing due to decreasing birth rates and increasing life expectancy. To sustain the German pension system, legal retirement age is increased step by step to 67 years. This raises questions about how to enable and motivate older individuals to work that long. Hence, it is important to understand whether they represent a homogeneous group that can be addressed through specific measures and instruments. Life-span theory points to systematic changes as well as increased heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 93 publications
1
5
0
1
Order By: Relevance
“…This was also found in Nigeria. Finally, a study in Germany found that life satisfaction was reduced with an increase in age (Thieme & Dittrich, 2015). This is also part of the findings of this study.…”
Section: International Journal Of Social Science Researchsupporting
confidence: 83%
See 1 more Smart Citation
“…This was also found in Nigeria. Finally, a study in Germany found that life satisfaction was reduced with an increase in age (Thieme & Dittrich, 2015). This is also part of the findings of this study.…”
Section: International Journal Of Social Science Researchsupporting
confidence: 83%
“…Therefore, it is an aspect of the quality of life or subjective well-being of individuals that is based on life experiences and events (Dyrdal et al, 2011;Hlavac, 2011;Steger & Kashdan, 2007). The effective evaluation examines the measurement of anger, worry, or happiness while cognitive evaluation assesses income, work, or health (Thieme & Dittrich, 2015). Life satisfaction, the focus of this study has been defined as a cognitive component of subjective wellbeing and plays an important role in positive life outcomes among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with life and with health were determined in 2019, 2020, and 2021 by the valid [27] single items "How satisfied are you currently with your life?" and "How satisfied are you with your health?…”
Section: Methodsmentioning
confidence: 99%
“…Chính điều này góp phần làm tăng sự hài lòng với cuộc sống của NCT. Đánh giá sự hài lòng của NCT không chỉ bằng những nhận thức chủ quan mà còn đánh giá thông qua kết quả các hoạt động sống cụ thể [12][13]. Sử dụng thời gian nhàn rỗi được xem kết quả của hoạt động sống cụ thể và điều này có nghĩa rằng, đánh giá sự hài lòng của NCT về cuộc sống có thể thông qua kết quả sử dụng thời gian rỗi.…”
Section: Mở đầU *unclassified